A multicenter study of ICU resource utilization in pediatric, adolescent and young adult patients post CAR-T therapy - Ragoonanan, Dristhi; Bhar, Saleh; Mohan, Gopi; Beltramo, Fernando; Khazal, Sajad J.; Hurley, Caitlin; Andersen, Clark; Margossian, Steven; Neelapu, Sattva S.; Shpall, Elizabeth; Gutierrez, Cristina; Tewari, Priti; et al. (Frontiers in Oncology, 2022)
Tisagenlecleucel, is associated with remarkable outcomes in treating patients up to the age of 25 years with refractory B-cell acute lymphoblastic leukemia (ALL). Yet, due to unique and potentially life-threatening complications, access remains limited to higher-resource and certified centers. Reports of inequity and related disparities in care are emerging. In this multi-center study of ALL patients admitted for anti-leukemia therapy, who required pediatric intensive care (ICU) support (n=205), patients receiving tisagenlecleucel (n=39) were compared to those receiving conventional chemotherapy (n=166). Median time to ICU transfer was 6(0-43) versus 1 (0-116) days respectively (p<0.0001). There was no difference in the use of vasopressor, ionotropic, sedating and/or paralytic agents between groups, but use of dexamethasone was higher among tisagenlecleucel patients. Patients receiving tisagenlecleucel were more likely to have cardio-respiratory toxicity (p=0.0002) but there were no differences in diagnostic interventions between both groups and/or differences in ICU length of stay and/or overall hospital survival. Toxicities associated with tisagenlecleucel are generally reversible and our findings suggest that resource utilization once admitted to the ICU may be similar among patients with ALL receiving tisagenlecleucel versus conventional chemotherapy. As centers consider improved access to care and the feasibility of tisagenlecleucel-certification, our study may inform strategic planning.